Does prior exposure of litter material affect the behaviour and substrate choices in Japanese quail (Coturnix japonica)? - Mohd Shukri, Muhammad Ishamuddin (2016)
An experiment has been conducted to observe whether prior exposure of particular bedding will affect the bedding preference and behaviour of Japanese quails. Rice straw, shredded brown paper, sand and wood shavings were focused in this experiment. From the result, for changes of behaviour, we can conclude that certain behaviours were related to the substrate exposed such as dust-bathing behaviour was preferred to be completed in sand while lying behaviour was preferred on rice straw. Besides that, sitting behaviour was mostly found on wood shaving and sand. Other behaviours were not really related to substrates, indeed they were performed on any substrates. For substrate preference, we can conclude that quails are more preferred to rice straw and wood shaving rather than shredded brown paper and sand.